TECHNOLOGIES FOR DEVELOPING ELECTRONIC TEXTBOOKS USING AUTOPLAY MEDIA STUDIO (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the technologies and methodological approaches for developing electronic textbooks using Autoplay Media Studio. Electronic textbooks have become an essential component of modern digital education, providing interactive, multimedia-rich learning environments. Autoplay Media Studio is a powerful authoring tool that enables educators and developers to create interactive electronic learning materials without deep programming knowledge. The article discusses the conceptual foundations of electronic textbooks, the functional capabilities of Autoplay Media Studio, stages of e-textbook development, multimedia integration, interactivity tools, and practical advantages of using this software in educational institutions. Visual diagrams are included to illustrate the structure and development process of electronic textbooks.